Structural identification of the multidimensional object according to the actual experiment - Блохін, Л. М.; Держак, С. В. (Proceedings of National Aviation University (archive), 2002)
The problem of structural identification of the dynamics of a multidimensional object is considered gives an opportunity to compile the basic provisions of the methodology for calculating optimal estimates the dynamic characteristics of the multidimensional object and the external object acting on it perturbation according to the experiment in normal operating modes.